(untitled) (Bioscience Journal, 2013)
The conversion of waste cooking oil into riboflavin by Ashbya gossypii was investigated in this paper. The effect of initial pH and the original volume of added waste cooking oil in the medium were evaluated to optimize the fermentation efficiency. The results show that when the initial pH was adjusted to 6.5 and 40 g/L waste cooking oil was added in the medium, no residual waste cooking oil was observed and the riboflavin yield reached 4.78 g/L. During the fermentation process, pH, biomass, free amino nitrogen and reduced sugar were dynamically monitored to evaluate the efficient utilization of waste cooking oil for riboflavin yield. The results show that when pH was kept in the range of 6.5-6.8 during the fermentation process, the levels of free amino nitrogen and reduced sugar could be used more efficiently and the riboflavin yield increased to 6.76 g/L .